PENGARUH KARAKTERISTIK INDIVIDU, KARAKTERISTIK PEKERJAAN, DAN KARAKTERISTIK SITUASI KERJA TERHADAP TINGKAT KEPUASAN KERJA KARYAWAN - Dewi, Dian Ayu Liana (potensio, 2012)
The research aims to test the effect of individual characteristic, job characteristic, and job ofsituation characteristic to level of job satisfaction official employee. This study uses the entirepopulation of the official employee CV. Karya Pemuda Semarang obtained 104 people. Thedata analysis technique used is linear regression. Results of research refer that the individualcharacteristic, job characteristic, and job of situation characteristic have an influence positive tolevel of job satisfaction official employee.Keyword: Individual characteristic, Job characteristic, and Job of situation characteristic,Level of job satisfaction official employee.